Some New Classes of Generalized Difference Strongly Summable n-Normed Sequence Spaces Defined by Ideal Convergence and Orlicz Function - Adem Kılıçman; Stuti Borgohain (Abstract and Applied Analysis)
We study some new generalized difference strongly summable n-normed sequence spaces using ideal convergence and an Orlicz function in connection with de la Vallèe Poussin mean. We give some relations related to these sequence spaces also.